Association between percentage of obese people and water hardness in water purification plants. (September 2020) - Shimoda, Yoko; Okada, Junichi; Yamada, Eijiro; Okada, Kazuya; Okada, Shuichi; Yamada, Masanobu
Abstract: In 1974, the significant association between the softness of water and the death rate due to cardiovascular diseases was reported. Recently, the association of excessive hard water consumption, body mass index, and waist circumference with the risk of hypertension was described among individuals living in regions supplied with hard and soft water. The risk was low in people living in regions with high water hardness. Thus, there was a conflicting result with regard to the effects of water hardness on metabolic syndrome. Therefore, we investigated the association between water hardness and the percentage of obese people. We utilized the annual report of Kenko 21 and water quality inspection data of Maebashi City, Japan, which is the prefectural capital of Gunma Prefecture belonging to the Kanto plain and located approximately 100 km north of Tokyo. The population of Maebashi City is 336, 154. In this study, data from 9 of 15 regions (Kasukawa, Miyagi, Souzya, Ogo, Haga, Eimei, Shikishima, Fujimi, and Kiyosato) in Maebashi City were analyzed. A significant negative correlation was observed between the percentage of obese people and water hardness in water purification plants. Thus, even in the soft water range, water hardness affects the percentage of obese people. Our results could provide a hint for the prevention and treatment of obesity regarding the importance of not only nutrition but also water quality. However, further studies involving more number of subjects are needed to confirm our results at a global scale. Highlights: A significant negative correlation was detected between the percentage of obese people and water hardness in water purification plants. Our results could provide an idea regarding the prevention and treatment of obesity according to the importance of not only nutrition but also water quality.